1998
DOI: 10.1002/pen.10205
|View full text |Cite
|
Sign up to set email alerts
|

Segmented block copolymers of natural rubber and propylene glycol‐toluene diisocyanate oligomers

Abstract: Segmented block copolymers were synthesized from hydroxyl terminated liquid natural rubber (HTNR) and polyurethane oligomers based on 1,2‐propylene glycol and toluene diisocyanate (TDI) by one‐shot and two‐shot processes in solution. They were completely phase segregated. Structural features were characterized by infrared and nuclear magnetic resonance spectroscopies. The two‐phase morphology was deducted from thermal analysis and dynamic mechanical analysis (DMA). The soft segment glass transition temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…7 Poly(ether-ester)s and poly(ester-ester)s are two types of segmented copolymers with a wide range of applications. 8 Some of these copolymers show a single glass transition temperature (T g ) that is intermediate between the T g s of the pure components. 3 For these materials, the evolution of the copolymer T g with respect to hard or soft segment composition has been successfully described by mixing rules used for compatible copolymers 9 (as Gordon-Taylor equation).…”
Section: Introductionmentioning
confidence: 99%
“…7 Poly(ether-ester)s and poly(ester-ester)s are two types of segmented copolymers with a wide range of applications. 8 Some of these copolymers show a single glass transition temperature (T g ) that is intermediate between the T g s of the pure components. 3 For these materials, the evolution of the copolymer T g with respect to hard or soft segment composition has been successfully described by mixing rules used for compatible copolymers 9 (as Gordon-Taylor equation).…”
Section: Introductionmentioning
confidence: 99%
“…On comparing the T g values of these samples with those of the polyurethane elastomers based on aliphatic chain extenders, 20 such as ethylene glycol (EG), propylene glycol (PG), 18 1,3-butane diol (1,3-BDO), and 1,4-butane diol (1,4-BDO), it is observed that the methyl and phenyl groups in BPA have got some remarkable influence in their thermal properties. Table III presents a comparative account of the T g values of various polyurethanes.…”
Section: Differential Scanning Calorimetrymentioning
confidence: 97%
“…[14][15][16] The two types of segments, viz., the NR and polyurethane are termed as the soft and hard segments, respectively. NR behaves as the soft segment due to its inherent flexibility.…”
Section: Copolymer Synthesismentioning
confidence: 99%
“…[14][15][16] Required stoichiometric amount of HTNR (Table I) was dissolved in chloroform (25% w/v), DBTDL catalyst, quantity of which was noted in a later section, viz., ''Copolymer synthesis'', was added and the solution was brought to reflux at 60-658C. The final stoichiometric amount of MDI in chloroform (25% w/v) was dropped into it over a period of 30 min, followed by one and a half hour reaction to endcap the HTNR.…”
Section: Synthesis Of Block Copolymersmentioning
confidence: 99%
See 1 more Smart Citation